Synthesis of nanosized Cr2O3 from turkish chromite concentrates with sodium borohydride (NaHB4) as reducing agent - AKTAŞ, SERDAR (ELSEVIER SCIENCE BV, 2016)
In this work, we investigated chromium extraction using a pyrometallurgical process and the subsequent production of nano-sized chromium oxide from Turkish chromite concentrate by assessing the effects of the base amount, fusion temperature, and fusion time on the chromium conversion. Nano-sized chromium oxide (Cr2O3) can be employed in many applications, such as catalysis, wear resistant materials, and advanced colorants, etc. To convert Cr(III) to Cr(VI) in the form of potassium chromate, potassium hydroxide (KOH) was employed under air flowing at a rate of 20.0 L/min. The kinetics of conversion from Cr(III) to Cr(VI) were also explored. Dissolution of the resulting potassium chromate in distilled water and pH neutralization afforded precipitation of aluminum hydroxide, which could be removed by filtration. The Cr(VI) in solution was subsequently converted to Cr(III) using sodium borohydride. The resulting chromium hydroxide was converted to nano sized chromium oxide by heating at ambient pressure and temperatures between 1073 K and 1473 K. Heating to lower temperatures was found to be associated with a smaller particle size. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Chromium; Chromite Concentrate; Sodium Borohydride; Reduction; MECHANICAL ACTIVATION; POTASSIUM HYDROXIDE; ORE; REDUCTION; OXIDE; WATER